Mini Poster Berbahasa Daerah sebagai Alternatif Media Promosi Kesehatan Kepatuhan Mencuci Tangan - Yunik Andriani; Linda Suwarni; Iskandar Arfan (Sarana Ilmu Indonesia (salnesia), 2020)
The incidence of diarrhea in Prosperous Village has increased from year to year. One effort to prevent diarrhea is to wash hands with soap and running water after defecation, before preparing food, and before eating. This study aimed to look at the effectiveness of regionally-colored mini posters on the compliance of mothers washing their hands in Sejahtera Village. A quasy experimental design (quasy experiment) non-equivalent control group was used. The research sample of 30 people taken by quota sampling technique. The statistical test used was the T-Test and the Kruskall-Wallis Test with a 95% confidence level. The results showed there were significant differences in compliance of mothers washing their hands with soap and running water in the experimental group mounting regional-language mini posters and soaps, installing local-language mini posters only, and the control group at the time after defecation, before preparing food, and before eating between before and after the intervention (p value <0.05). The mini-poster media in local languages ??is effective in increasing compliance with mothers washing their hands. Regional language poster media can be an alternative in health promotion media for the prevention of primary disease.